The Effect of Work-Life Balance and Work Engagement on Employee Performance: A Literatur Review - Maghfiratika, Tishar; Pujiati, Herni (Dinasti Publisher, 2025)
Work-life balance and work engagement are key factors influencing employee performance in workplace settings. In the current highly competitive environment, companies need to enhance productivity and operational efficiency. Workers who effectively manage their work and personal lives often experience reduced stress and improved performance results. This equilibrium enhances job satisfaction while also bolstering employee loyalty, thereby boosting overall organizational efficiency. Moreover, individuals who are deeply involved in their work frequently attain remarkable outcomes as they tackle their responsibilities with heightened enthusiasm and responsibility. Still, numerous organizations struggle to establish an environment that fosters both work-life balance and employee involvement. The study titled